2019
DOI: 10.1111/pere.12266
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between relationship effectiveness, life stress, and sleep: A prospective study

Abstract: Research has shown that greater stress responses predict worse sleep and that the quality of one's current romantic relationship predicts one's sleep. Despite these established links, research has not examined connections between ongoing patterns of interpersonal experiences and competencies (relationship effectiveness) and stress exposure on sleep. Participants in the Minnesota Longitudinal Study of Risk and Adaptation (MLSRA) completed measures assessing relationship effectiveness and stress exposure at ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Among 443 Colombian university students, higher levels of satisfaction in one’s romantic relationship were found to be associated with reporting needing fewer hours of sleep to feel rested (Talero-Gutierrez et al, 2017). Also, Huelsnitz et al (2019) found that the impact of relationship functioning in young adults may have robust and enduring effects on sleep. Data from 112 individuals drawn from a longitudinal cohort study demonstrated that relationship effectiveness at age 23—the extent to which participants were judged to be "competently engaged in romantic relationships" (p. 81) by trained coders of recorded relationship history interviews—was associated with better subjectively rated sleep quality at age 37, but not sleep duration (Huelsnitz et al, 2019).…”
Section: Consequences Of Poor Sleep Qualitymentioning
confidence: 99%
“…Among 443 Colombian university students, higher levels of satisfaction in one’s romantic relationship were found to be associated with reporting needing fewer hours of sleep to feel rested (Talero-Gutierrez et al, 2017). Also, Huelsnitz et al (2019) found that the impact of relationship functioning in young adults may have robust and enduring effects on sleep. Data from 112 individuals drawn from a longitudinal cohort study demonstrated that relationship effectiveness at age 23—the extent to which participants were judged to be "competently engaged in romantic relationships" (p. 81) by trained coders of recorded relationship history interviews—was associated with better subjectively rated sleep quality at age 37, but not sleep duration (Huelsnitz et al, 2019).…”
Section: Consequences Of Poor Sleep Qualitymentioning
confidence: 99%